Use of social networks and psychological well-being in Pharmacy and Biochemistry students of a private university in Huancayo, 2023. - Jesus-Carbajal , Orlando (2024)
Objective: determine the relationship between the use of social networks and psychological well-being in Pharmacy and Biochemistry students at the Universidad Privada de Huancayo Franklin Roosevelt, 2023. Material and Methods: Basic correlational design study. The sample was 120 students from the Faculty of Pharmacy and Biochemistry, the data collection technique was the survey and the instruments were a structured questionnaire, the Spearman correlation coefficient was used. Results: 40% of the total students consider that the use of social networks is low; 45% thought that the use of social networks is medium and 15% thought that the use of social networks is high. 15% consider that they have low psychological well-being; 60% consider that they have moderate psychological well-being and 25% consider that they have high psychological well-being. There is a very high negative and significant correlation (Rho= -.878, p<0.05) between obsession with social networks and psychological well-being. There is a very high negative and significant correlation (Rho= -.783, p<0.05) between lack of personal control and psychological well-being. There is a very high negative and significant correlation (Rho= -.708**, p<0.05) between excessive use of social networks and psychological well-being. Conclusions: There is a very high negative and significant correlation (Rho=-.834, p<0.05) between the use of social networks and psychological well-being.